Analysis of the Compliance Level of Campaign Fund Reporting of the National Mandate Party in Central Sulawesi in 2024 - Amalyah, Ilfat Afia; Din, Muhammad; Jurana, Jurana; Masruddin, Masruddin (Jambura Equilibrium Journal, 2025)
This study aims to analyze the compliance level of the campaign fund reporting of Partai Amanat Nasional (PAN) of Central Sulawesi in 2024 based on the audit results. Using a quantitative descriptive approach, this study provides a comprehensive overview of the level of compliance and the factors that influence it. The study focuses on timeliness, completeness of documentation, and consistency of reported data with regulations set by the General Election Commission (KPU). Data was sourced from official audit reports and interviews with relevant stakeholders. The results show that the compliance rate of PAN in Central Sulawesi reached 98.3%, although there were certain constraints, especially related to the completeness of documents in certain districts. This study provides recommendations to improve the transparency and accuracy of campaign finance reporting in the future.